ANALISIS KINERJA USAHATANI DAN KESEJAHTERAAN PETANI SAYURAN DI KOTA PAGAR ALAM PROVINSI SUMATERA SELATAN - Suriaty Situmorang; Dwi Haryono; Achdiansyah Soelaiman (Indonesian Journal of Socio Economics, 2019)
This research aims to analyze vegetables farming performance and vegetables farmer household welfare in North Dempo Sub-District, Pagar Alam City, South Sumatera Province. Location of the research was chosen purposively and the samples is determined by simple random sampling method. The number of the samples are 99 household and each consist of 33 chili, mustrad greens, and cabbage farmers with monoculture farming. Therefore, this research used survey method. The result of the research shows that vegetables farming performance in the research location has been not-good, with : (1) average productivity of chili, mustard greens, and cabbage farming being 6.080kg/ha, 7.813kg/ha, and 9.557kg/ha, respectively. (2) Production capacity of chili, mustrad greens, and cabbage are 30,40%, 31,25%, and 38,23%, respectively. (3) Household average income in hectare in every growing season for chili, mustrad green, and cabbage are Rp 49.906.113,36, Rp 5.279.915,26, and Rp 9.289.519,69, respectively. Mayority of vegetables farmers welfare based on Sayogyo Proverty Criteria (1997) are in sufficient criteria. Furthermore, 72,73% chili farmers are in sufficient criteria and the rest (27,27%) are in well criteria, 84,85% mustrad greens farmers are in sufficient criteria and the rest (15,15%) are in well criteria, 78,79% cabbage farmers are in sufficient criteria and the rest (21,21%) are in well criteria.Keywords: farmer welfare; farming performance; vegetables farming